The oral-gut axis: Salivary and fecal microbiome dysbiosis in patients with inflammatory bowel disease - Mohamed M. H. Abdelbary; Maximilian Hatting; Alexandra Bott; Andrea Dahlhausen; Doris Keller; Christian Trautwein; Georg Conrads (Frontiers in Cellular and Infection Microbiology, 2022)
Inflammatory bowel disease (IBD) is a group of chronic inflammatory disorders that fall into two main categories: Crohn’s disease (CD) and ulcerative colitis (UC). The gastrointestinal tract extends from the mouth to the anus and harbors diverse bacterial communities. Several sequencing-based studies have identified an intestinal enrichment of oral-associated bacteria and demonstrated their ability to induce intestinal inflammation in mice, suggesting that intestinal pathobionts originate from the oral cavity, particularly members of the genus Streptococcus. This study aimed to investigate the composition of the salivary and fecal microbiome of IBD patients (n = 14) compared to healthy controls (n = 12) and to determine the abundance of common bacterial taxa in both niches. Metagenomic DNA was extracted from saliva and fecal samples, and the 16S rRNA gene was targeted for sequencing. Our results revealed that the overall microbial composition of saliva was significantly altered in the IBD patients compared to the control subjects (p = 0.038). At the genus level, Veillonella and Prevotella were highly abundant in IBD (median: 25.4% and 22.2%, respectively) compared to the control group (17.9% and 13.4%, respectively). In contrast, Neisseria, Streptococcus, Haemophilus, and Fusobacterium were associated with a healthy gut state. Regarding the fecal microbiome, the IBD group had a significantly higher abundance of Clostridium sensu stricto 1 and Escherichia-Shigella (both comprising pathogenic bacteria) compared with the control group. Members of both bacterial groups have previously been shown to positively correlate with intestinal inflammation and high expression of pro-inflammatory cytokines that disrupt intestinal barrier integrity. In addition, we demonstrate that the increased abundance of Clostridium sensu stricto 1 and Escherichia-Shigella has also been associated with significant upregulation of certain metabolic pathways in the feces of the IBD group, including bacterial invasion of epithelial cells. Streptococcus was the only common genus detected in both the salivary and fecal microbiome and represented the oral-gut axis in our study. Using culture-based methods, we isolated 57 and 91 Streptococcus strains from saliva as well as 40 and 31 strains from fecal samples of the controls and IBD patients, respectively. The phylogenetic tree of streptococci based on sodA sequences revealed several patient-specific clusters comprising salivary and fecal streptococcal isolates from the same patient and belonging to the same species, suggesting that the oral cavity is an endogenous reservoir for intestinal strains.